Catalogue of juvenile instars of oribatid mites (Acari: Oribatida)—the next decade (2014–2023) - Norton, Roy A.; Ermilov, Sergey G. (Zootaxa, 2024)
In its traditional, paraphyletic context (sans Astigmata), oribatid mites comprise more than 11,000 known species (Subías 2022). They are largely fungivores and decomposers in organic horizons of soil and have a plesiotypic ontogeny that includes four active, free-living juvenile instars. In a taxonomically organized 2014 catalogue, we summarized literature resources concerning the 805 species for which ontogenetic data (mainly morphological) were available. Herein, we supplement that catalogue with all data known to us that were published during the intervening decade. These relate to 267 species, of which 165 were described prior to 2014. As in the 2014 catalogue, representation is strongest among: the middle-derivative hyporder Nothrina; brachypyline superfamilies that are affiliated with aquatic, semiaquatic or intertidal environments (Limnozetoidea, Ameronothroidea); some eupheredermous groups (Plateremaeoidea, Damaeoidea); and Ceratozetoidea. Also as in 2014, groups that are underreprented, based on their high known diversity, are the ptyctimous Mixonomata (Euphthiracaroidea, Phthiracaroidea) and the brachypyline superfamilies Oppioidea and Oripodoidea.